The Current State of Research on PET Hydrolyzing Enzymes Available for Biorecycling - Kawai, Fusako (Catalysts, 2021)
This short paper reviews two groups of enzymes designated as polyethylene terephthalate (PET) hydrolases: one consists of thermophilic cutinases from thermophilic microorganisms (actinomycetes and a fungus) and the other consists of mesophilic cutinases, the representative of which is IsPETase from a mesophilic bacterium. From the viewpoint that PET hydrolysis requires a high temperature close to the glass transition temperature (65–70 °C in water) of PET, mesophilic cutinases are not suitable for use in the enzymatic recycling of PET since their degradation level is one to three orders of magnitude lower than that of thermophilic cutinases. Many studies have attempted to increase the thermostability of IsPETase by introducing mutations, but even with these modifications, the mesophilic cutinase does not reach the same level of degradation as thermophilic cutinases. In addition, this kind of trial contradicts the claim that IsPETase works at ambient temperature. As plastic pollution is an urgent environmental issue, scientists must focus on feasible thermophilic enzymes for the enzymatic processing of disposed PET, rather than on mesophilic cutinases. Thermophilic and mesophilic cutinases must be evaluated precisely and comparatively, based on their features that enable them to hydrolyze PET, with the aim of enzymatic PET disposal. The level of thermophilic cutinases has already reached their optimal level in PET biorecycling. The optimal level may be reached through the processing of PET waste, by amorphization and micronization into readily hydrolysable forms and the improvement of PET hydrolases by engineering higher degradation ability and low-cost production. Here I summarize the critical points in the evaluation of PET hydrolases and discuss the biorecycling of PET.